Two methods for assessment of choline status in a randomized crossover study with varying dietary choline intake in people: isotope dilution MS of plasma and in vivo single-voxel magnetic resonance spectroscopy of liver. Issue 6 (1st March 2021) - Horita, David A; Hwang, Sunil; Stegall, Julie M; Friday, Walter B; Kirchner, David R; Zeisel, Steven H
ABSTRACT: Background: Choline deficiency has numerous negative health consequences; although the preponderance of the US population consumes less than the recommended Adequate Intake (AI), clinical assessment of choline status is difficult. Further, several pathways involved in primary metabolism of choline are estrogen-sensitive and the AI for premenopausal women is lower than that for men. Objectives: We sought to determine whether in vivo magnetic resonance spectroscopy (MRS) of liver and/or isotope-dilution MS of plasma could identify biomarkers reflective of choline intake (preregistered primary outcomes 1 and 2, secondary outcome 1). Determination of whether biomarker concentrations showed sex dependence was a post hoc outcome. This substudy is a component of a larger project to identify a clinically useful biomarker panel for assessment of choline status. Methods: In a double-blind, randomized, crossover trial, people consumed 3 diets, representative of ∼100%, ∼50%, and ∼25% of the choline AI, for 2-wk periods. We measured the concentrations of choline and several metabolites using 1 H single-voxel MRS of liver in vivo and using 2 H-labeled isotope dilution MS of several choline metabolites in extracted plasma. Results: Plasma concentrations of 2 H9 -choline, unlabeled betaine, and 2 H9 -betaine, and the isotopic enrichment ratio (IER) of betaine showed highly significant between-diet effects ( q < 0.0001), with unlabeled betaine concentration decreasing 32% from highest to lowest choline intake. Phosphatidylcholine IER was marginally significant ( q = 0.03). Unlabeled phosphatidylcholine plasma concentrations did not show between-diet effects ( q = 0.34). 2 H9 (trimethyl)-phosphatidylcholine plasma concentrations ( q = 0.07) and MRS-measured total soluble choline species liver concentrations ( q = 0.07) showed evidence of between-diet effects but this was not statistically significant. Conclusions: Although MRS is a more direct measure of choline status, variable spectral quality limited interpretation. MS analysis of plasma showed clear correlation of plasma betaine concentration, but not plasma phosphatidylcholine concentration, with dietary choline intake. Plasma betaine concentrations also correlate with sex status (premenopausal women, postmenopausal women, men). This trial was registered at clinicaltrials.gov as NCT03726671.